Bolsonaro and pandemic denial: Some considerations on the leader, anti-intellectualism, and nationalism. Issue 6 (12th May 2022) - Anonymous,
Abstract: On the 9 th of May 2020 The Lancet, the leading medical journal, published an editorial referring to the current situation of the pandemic in Brazil, which is short of being disastrous, and describing Jair Bolsonaro, the Brazilian president, as the biggest threat to Brazil – we would add to the world. In this paper, we enquire the issue of leadership, anti-intellectualism and nationalism by conducting a philosophical enquiry, whilst also questioning the role and shortcomings of the Brazilian educational system in sowing the seeds, and allowing this situation to develop in the country. This philosophical enquiry does not attempt to lay blame on the Brazilian educational system; rather, it is an attempt, an urge for reflection and self-reflection, so that the errs of the past may be remediated in the future; hopefully, a near future.